Indonesian Capital Market Reactions Post Covid 19 Pandemic To National Political Events (Event Study on LQ45 Shares for the Period Before the 2024 Presidential Election) - Linda Grace Loupatty; Dewi Nidia Soepriadi; Trisna Sari Lewaru; Eric Piterson Radjawane (Jurnal Akuntansi Indonesia)
The aim of this research is to test and analyze whether there is a difference in the average abnormal return and average trading volume activity before and after the announcement of the determination of the 2024-2029 Indonesian Presidential Candidate pair on the LQ 45 index shares. The research was conducted at the IDX on shares of the LQ45 issuer. so the sample is 45 companies. This research is event research with a quantitative approach. The data used in this research is secondary data, namely in the form of annual reports of companies listed on the Indonesia Stock Exchange (BEI) in the LQ45 Index category during the event period or window event period. The event date is 13 November 2023. And the event window is from 02 November 2023 to 22 November 2023. This study uses the Paired Sample t-Test to test whether there is a difference in the average abnormal return and average trading volume activity before and after the event . Announcement of the Determination of Candidate Pairs for President of the Republic of Indonesia 2024-2029, with a significance level of a= 5%. The research results show that there is no difference in the Average Abnormal Return and Average Trading Volume before and after the announcement of the determination of the 2024-2029 Presidential Candidates on the LQ 4 index shares.